Bioerodable PLGA-Based Microparticles for Producing Sustained-Release Drug Formulations and Strategies for Improving Drug Loading - Han, Felicity Y.; Thurecht, Kristofer J.; Whittaker, Andrew K.; Smith, Maree T. (Frontiers in Pharmacology, 2016)
Poly(lactic-co-glycolic acid) (PLGA) is the most widely used biomaterial for microencapsulation and prolonged delivery of therapeutic drugs, proteins and antigens. PLGA has excellent biodegradability and biocompatibility and is generally recognized as safe by international regulatory agencies including the United States Food and Drug Administration and the European Medicines Agency. The physicochemical properties of PLGA may be varied systematically by changing the ratio of lactic acid to glycolic acid. This in turn alters the release rate of microencapsulated therapeutic molecules from PLGA microparticle formulations. The obstacles hindering more widespread use of PLGA for producing sustained-release formulations for clinical use include low drug loading, particularly of hydrophilic small molecules, high initial burst release and/or poor formulation stability. In this review, we address strategies aimed at overcoming these challenges. These include use of low-temperature double-emulsion methods to increase drug-loading by producing PLGA particles with a small volume for the inner water phase and a suitable pH of the external phase. Newer strategies for producing PLGA particles with high drug loading and the desired sustained-release profiles include fabrication of multi-layered microparticles, nanoparticles-in-microparticles, use of hydrogel templates, as well as coaxial electrospray, microfluidics and supercritical carbon dioxide methods. Another recent strategy with promise for producing particles with well-controlled and reproducible sustained-release profiles involves complexation of PLGA with additives such as polyethylene glycol, poly(ortho esters), chitosan, alginate, caffeic acid, hyaluronic acid and silicon dioxide.